The Elements of Customer Relationship Management and Their Impact on Customer Satisfaction: A Study of Five-Star Hotels in Malaysia - Mohd Baharieman, Nur Sufi Nadhira; Azwan, Luqman Hakim Shamsul; Ngah, Haslina Che; Nawawi, Wan Nazriah Wan; Ishak, Farah Adibah Che (Information Management and Business Review, 2025)
Customer satisfaction is a crucial factor for the success of any business. One of the most significant challenges within the hospitality industry is identifying effective strategies to satisfy and retain customers. The purpose of this study was to examine the relationship between key elements of customer relationship management (CRM)—specifically quality of service, access to service, and service features—and their impact on customer satisfaction at five-star hotels in Malaysia. The study aimed to determine the extent to which CRM enhances overall customer satisfaction. Employing a quantitative research design, data were collected through structured questionnaires from 384 local guests who had stayed at five-star hotels in Malaysia. The results reveal a significant positive correlation between the identified CRM elements and customer satisfaction. Notably, quality of service emerged as the most influential element, followed by access to services and the availability of service features. These findings underscore the critical importance of delivering high-quality service, ensuring seamless access to amenities, and providing comprehensive service features to enhance customer satisfaction. The study highlights the importance of implementing effective CRM strategies at five-star hotels to foster customer loyalty and maintain a competitive edge in Malaysia’s dynamic hospitality sector.